Experimental investigation on axial velocity distribution for ship’s twin-propeller jets - Yew, W.T.; Hashim, Roslan; Ng, K.C. (Taylor & Francis, 2017)
The investigation of twin-propeller jets as ships undergo acceleration is essential. This form of jet has been triggering problematic consequences such as seabed scouring. In order to prevent such scouring, near-bed velocities must first be analyzed in order to design the necessary protection when the under keel clearance of a ship is low when it is near port structures. This paper presents experimental work performed by Laser Doppler Anemometry. It is noticed that research into twin-propeller jet profiles still remains limited in the literature. Therefore, we intend to analyze twin-propeller axial velocity profiles and look into several flow characteristics such as efflux velocity and its decay pattern. Also, the measured velocity profile is compared to that of a single-propeller jet. Current results show that scouring is more severe in the case of the twin-propeller jets.